Adjacent skin rotation flap for large defect in primary breast tumor. Issue 7 (7th October 2018) - Jin, Liting; Wu, Xinhong; Zha, Li; Feng, Yaojun; Xu, Juan; Zheng, Hongmei; Shao, Jun; Zhao, Minjian; Cui, Xiaojiang; Giuliano, Armando E.; Gong, Yiping
Abstract: Backgrounds: Surgical resection of large primary breast tumor often results in large chest wall defects. The purpose of this study is to evaluate the feasibility of using adjacent skin rotation (ASR) flap in patients with giant primary breast tumor. Methods: A total of 26 giant primary breast tumor patients treated with ASR flap were included in this study. The postoperative conditions, including operating time, blood loss, length of hospital stay, and clinical complications were observed. Meanwhile, the information on 17 breast tumor patients treated with transverse rectus abdominis myocutaneous (TRAM) flap were collected and assigned to a control group. Results: The mean defect size after mastectomy was 16.7 × 13.4 cm, while the median follow‐up period was 13 months after surgery. A total of 15.4% patients had developed with local complications, and one of them had more than one complication. When comparing the postoperative outcomes, statistically significant differences were found between the two groups with respect to operating time, blood loss, and length of hospital stay ( P  < 0.001). Conclusions: ASR flap is a reliable technique for immediate reconstruction of massive chest wall defects in patients with giant primary breast tumor.